AUDIT KAS DAN BANK SERTA PENYUSUNAN LAPORAN KEUANGAN - Augustpaosa Nariman; Alan Octama Massidy (PROSIDING SERINA, 2021)
Financial transactions carried out by individuals and companies will always be related to cash and banks. Along with the increase in information technology, quality information is needed and is free from material misstatements. The need for financial information makes accountants increasingly challenged to continuously improve their abilities. Tiara Kasih High School students located in West Jakarta, class XII, need the latest knowledge and understanding of accounting includes recording, auditing, and financial reports. Financial transactions through cash and banks are very important for auditing so that all financial transactions are in accordance with regulations and no fraudulent acts in the use of cash and banks. Lecturer from FEB Untar and based on an invitation from Tiara Kasih High School Jakarta to provide audit training on cash and bank transactions. The training fund comes from LPPM UNTAR to provide soft skills in the form of training and Accounting Modules along with practice questions. This PKM activity is carried out online through a webinar organized by the school which is attended by teachers and class XII students. In the training, financial accounting exercises were also provided, accompanied by a question and answer session and discussion. The purpose of this training is to prepare students of Tiara Kasih Christian High School Jakarta with an understanding of financial accounting, cash and bank audits, financial reports in order to gain a thorough knowledge of accounting and auditing, how to audit cash transactions and banks which are  actually routine transactions carried out by individuals, organizations, and companies.